2023
DOI: 10.3390/v15081732
|View full text |Cite
|
Sign up to set email alerts
|

Current ARTs, Virologic Failure, and Implications for AIDS Management: A Systematic Review

Abstract: Antiretroviral therapies (ARTs) have revolutionized the management of human immunodeficiency virus (HIV) infection, significantly improved patient outcomes, and reduced the mortality rate and incidence of acquired immunodeficiency syndrome (AIDS). However, despite the remarkable efficacy of ART, virologic failure remains a challenge in the long-term management of HIV-infected individuals. Virologic failure refers to the persistent detectable viral load in patients receiving ART, indicating an incomplete suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…However, due to the challenges involved in diagnosing the condition and the various reasons why ARV failure occurs, the burden of treatment failure is not extensively documented [6]. HIV drug resistance, inadequate dose, drug interactions, poor adherence, and inadequate medication absorption are important contributing factors that lead to antiretroviral (ARV) therapy failure that should be recognized and addressed [7]. To overcome this precarious predicament, a more effective approach must be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the challenges involved in diagnosing the condition and the various reasons why ARV failure occurs, the burden of treatment failure is not extensively documented [6]. HIV drug resistance, inadequate dose, drug interactions, poor adherence, and inadequate medication absorption are important contributing factors that lead to antiretroviral (ARV) therapy failure that should be recognized and addressed [7]. To overcome this precarious predicament, a more effective approach must be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…The last updated World Health Organization (WHO) report indicated that globally about 39.0 million people acquired HIV-1 and 630,000 people died from HIV-1-dependent problems at the end of 2022 [5]. Furthermore, HIV-1/AIDS provokes opportunistic infections including tuberculosis, cryptococcal infection, histoplasmosis, and severe bacterial infections; hepatitis B, and C co-infections [6][7][8]; and comorbidities such as cardiovascular, kidney, and liver disorders and cancer [9]. In the near future, COVID-19 and monkeypox virus infections could be possible challenges for clinicians and people with HIV-1 [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…When the CD4+ T cell count drops below 200 cells/mm 3 , HIV is said to have progressed to AIDS. Antiretroviral therapy (ART) continues to be the standard treatment for HIV/AIDS, often consisting of various classes of ART drugs used in combination to suppress viral activity, enhance immune activity, and prevent disease progression [7]. A standard HIV regimen includes a combination of three anti-HIV medications from a minimum of two Viruses 2024, 16, 321 2 of 13 drug classes.…”
Section: Introductionmentioning
confidence: 99%
“…A standard HIV regimen includes a combination of three anti-HIV medications from a minimum of two Viruses 2024, 16, 321 2 of 13 drug classes. ART is not curative; however, it has been shown to reduce HIV transmission and prolong the lives of those living with HIV [7].…”
Section: Introductionmentioning
confidence: 99%